Potential and limitations of wastewater reuse in the Hashemite Kingdom of Jordan = Możliwości i ograniczenia wykorzystania ścieków oczyszczonych w Jordanii - Myszograj, Sylwia; Qteishat, Omar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Jordan represents a typically water constrained economy that is daily confronted with decisions on its water use. With a fast growing population and an expanding agricultural sector, the demand for alternatives of fresh water resources remains imminent. An important strategy for the Jordanian government is to meet the water demand for agricultural sector by producing more treated wastewater.
Keywords: bilans wód; wykorzystanie ścieków oczyszczonych; Jordania - gospodarka wodna; water balance; wastewater reuse; agriculture; Jordan